Japan : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2009)
This paper focuses on observance of standards and codes on the Financial Action Task Force (FATF) recommendations for antimoney laundering and combating the financing of terrorism (AML/CFT) measures in Japan. The paper describes and analyzes such measures and provides recommendations on how certain aspects of the system could be strengthened. It also sets out the levels of compliance of Japan with FATF recommendations and also provides recommendations on how certain aspects of the system could be strengthened.